United Nations conference on trade and development: Handbook of world mineral trade statistics 1991 - 1996 (United Nations, 1999)
The book provides consistent data at the world, regional and country levels for international trade in the major non-fuel minerals and metals, from primary to semi-processed forms. It provides both quantities and values for these products. It includes summary tables on the value of world exports and imports of minerals, ores and metals, by country and region, by the items of the Standard International Trade Classification as well as detailed tables concerning thirty-eight minerals and metals representing 97 per cent of the 1996 world trade of mineral and metal commodities. A special table presents the valuation of the 1995 world non-fuel mineral production by commodity and country.